2005
DOI: 10.1002/app.21829
|View full text |Cite
|
Sign up to set email alerts
|

Methacryloylpropyl–βcyclodextrin and vinylpyrrolidone copolymers: Synthesis and characterization as potential chiral selector

Abstract: ABSTRACT:The free radical copolymerization of vinylpyrrolidone (VP) with 2-hydroxy-3-methacryloyloxypropyl ␤-cyclodextrin (␤W7 MAHP), a derivative of hydroxypropyl ␤-cyclodextrin (CD) substituted by polymerizable methacryloyl groups, is carried out in water by varying the molar ratio of the comonomers. It is found that the higher the molar ratio of ␤W7 MAHP to VP, the larger the molar mass of the water-soluble copolymer. A size exclusion chromatography analysis coupled with multiangle laser light scattering de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Thus, CD derivatives based on the initial copolymer VP-AA are water soluble at a low content of CD residues (0.6-1.2 mol %, 6-12 wt %) (Table 3, experiments 11,12,[17][18]. An increase in the CD content in the polymer to 6.7 mol % (43 wt %) ( Table 3, experiment 16) leads to the loss of polymer solubility in water.…”
Section: Nh 4 Ohmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, CD derivatives based on the initial copolymer VP-AA are water soluble at a low content of CD residues (0.6-1.2 mol %, 6-12 wt %) (Table 3, experiments 11,12,[17][18]. An increase in the CD content in the polymer to 6.7 mol % (43 wt %) ( Table 3, experiment 16) leads to the loss of polymer solubility in water.…”
Section: Nh 4 Ohmentioning
confidence: 99%
“…In particular, soluble poly meric derivatives of cyclodextrins based on poly(acrylic acid) [5], on copolymers of acrylic acid (AA) and acrylamide [6], and on polyallylamine [7] and crosslinked polymers [8] were synthesized via reactions in polymer chains. Soluble and crosslinked cyclodextrin containing polymers were prepared through the radical copolymerization of unsaturated derivatives of cyclodextrins with some monomers, including N vinylpyrrolidone (VP) [4,[9][10][11][12][13][14]. It was 1 shown that the polymeric derivatives of cyclodextrins can form inclusion complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Matrices consisting of porous particles have a large area of interaction with the liquid phase, which is a key element in efficient separation. Cyclodextrins and derivatives hereof grafted to porous particles, for example silica gel, have gained some attention as cyclodextrins are able to facilitate the separation of structural isomers [16][17][18]. Commonly used methods to characterize cyclodextrin modified particles include Fourier Transformed Infrared Spectroscopy (FTIR) [13,19,20], Raman Spectroscopy [16,21], Scanning Electron Microscope (SEM) [13,16,20,22], Elemental Analyses [21,23,24] and Thermo Gravimetric Analysis (TGA).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In addition to brush-type CSPs based on low-molecular-mass selectors, [3][4][5][6][7][8] a large number of CSPs containing surface-adsorbed polysaccharide derivatives, especially cellulose and amylose carbamates, have been used extensively at the analytical and preparative levels because they can resolve the enantiomers of a wide range of racemic compounds by high-performance liquid chromatography (HPLC). [9][10][11][12][13][14][15][16][17] At the same time, research on CSPs based on synthetic, optically active polymers has also been rapidly evolving. [18][19][20][21][22][23][24][25][26] Some columns packed with polymeric CSPs have been commercial-ized.…”
Section: Introductionmentioning
confidence: 99%
“…The chromatographic separation of enantiomers of chiral stationary phases (CSPs) has attracted great attention as one of the most efficient separation techniques 1, 2. In addition to brush‐type CSPs based on low‐molecular‐mass selectors,3–8 a large number of CSPs containing surface‐adsorbed polysaccharide derivatives, especially cellulose and amylose carbamates, have been used extensively at the analytical and preparative levels because they can resolve the enantiomers of a wide range of racemic compounds by high‐performance liquid chromatography (HPLC) 9–17. At the same time, research on CSPs based on synthetic, optically active polymers has also been rapidly evolving 18–26.…”
Section: Introductionmentioning
confidence: 99%